Miliary Tuberculosis Presenting as Puerperial Fever - A. Agarwal (Case Reports in Infectious Diseases)
Miliary tuberculosis as a cause of puerperial fever is extremely rare. It is a serious illness with nonspecific clinical manifestations and typical chest radiographic findings may not be seen until late in the course of the disease. It is often associated with maternal immunocompromised status. Here, we report a case of miliary tuberculosis in a nonimmunocompromised mother presenting as fever of unknown origin in immediate puerperium. Prolonged workup of eight weeks led to the diagnosis of miliary tuberculosis as the cause of postpartum fever that responded well to antituberculous drugs.